Paroles reprises, erreur et fluence dans les narrations orales spontanées des apprenants de français langue étrangère - Theophanous, Olga; Perez-Bettan, Annie; Hilton, Heather (My University, 2014)
This paper reports a study that investigated self-corrections in spontaneous oral narratives. Seventeen adults students of French as a foreign language were asked to imagine the story from a cartoon and a short silent film. Their performances were recorded and then transcribed. The corpus obtained contains 17255 words. The aim of the study is to provide surface descriptions and classifications of self-corrections and to determine their relationships to linguistic error. Four major types of self-corrections were distinguished: morphological, syntactic, semantic and lexical. The analysis shows that self-corrections are not only a mecanism used to repair errors but also a strategy used by the learners to buy time for lexical search and to promote greater oral fluency. Different cases of improved fluency via self-corrections are discussed, where prefabricated language also seems to play a strategic role.